1990
DOI: 10.1002/1520-6629(199010)18:4<361::aid-jcop2290180409>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A multimedia-based approach to increasing communication and the level of AIDS knowledge within families

Abstract: The print and electronic media have been used effectively in the past to assist individuals in altering negative health behaviors and attitudes associated with obesity, stress, hypertension, and smoking. This article presents the use of a multimedia‐based, health promotion strategy targeted toward AIDS prevention within the family unit. In November of 1988, for 6 consecutive days, 5‐ to 10‐minute segments addressing AIDS and the family were televised on the noon and 9 p.m. news broadcasts of a major television… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…44,47,52,53,55 No change was noted in 1 study. 46 Four studies assessed adolescent reports of changes in the frequency of communication: 2 resulted in increases 47,53 ; the adolescent result was not reported for 1 study 52 ; and 1 resulted in no change. 46 Only 1 study compared the magnitude of change in the frequency of communication between parents and adolescents; parents reported a larger change than adolescents.…”
Section: Frequency Of Communicationmentioning
confidence: 88%
See 4 more Smart Citations
“…44,47,52,53,55 No change was noted in 1 study. 46 Four studies assessed adolescent reports of changes in the frequency of communication: 2 resulted in increases 47,53 ; the adolescent result was not reported for 1 study 52 ; and 1 resulted in no change. 46 Only 1 study compared the magnitude of change in the frequency of communication between parents and adolescents; parents reported a larger change than adolescents.…”
Section: Frequency Of Communicationmentioning
confidence: 88%
“…MQSs ranged from 6 to 16 points (mean: 12 Ϯ 3) ( Table 4). Only 1 study had an MQS in the lower-quality range 54 ; 7 were of medium quality, 44,46,48,49,51,52,55 and 4 were of high quality. 45,47,50,53 Reliability/Validity Assessment Studies infrequently reported validity or reliability data for the measures used to assess study outcomes.…”
Section: Methodologic Qualitymentioning
confidence: 99%
See 3 more Smart Citations